AERA OTL 2022 Special Issue Introduction - Qian Xu; Jennifer Richardson; Patrick Lowenthal (Online Learning, 2022)
The American Educational Research Association (AERA) is a research society that “strives to advance knowledge about education, to encourage scholarly inquiry related to education, and to promote the use of research to improve education and serve the public good” (2022). The association aims to encourage educational research studies and promote the practical implications of research findings. With 12 divisions and more than 150 special interest groups (SIGs), AERA provides advanced information to generate connections across practitioners, the field’s leading researchers, and policymakers. AERA includes more than 25,000 members from 85 countries, including faculty, researchers, evaluators, graduate students, university deans, research directors, and higher education administrators.